2015
DOI: 10.3126/ajms.v7i2.13049
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hypoxemia in children associated with pneumonia

Abstract: Background and Objectives:The most severe manifestation of pneumonia is hypoxemia has been shown to be a risk factor for morbidity and mortality. Authors investigated associating factors and determinants of hypoxemia in children with pneumonia. Materials and Methods: A crosssectional study is designed among children of pediatric outpatient and emergency department that enrolled at Government Multi-Speciality Hospital, Chandigarh. One hundred fi fty children recruited for study. The demographic and clinical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
2
2
2
Order By: Relevance
“…The high sensitivity of fever, difficulty in breathing and cough was comparable with previous studies, while inability to feed was found specific as supported by Sah HD. 17,20,23 Findings of the present study revealed that cyanosis had a very high association whereas grunting; chest retractions, nasal flaring and impaired consciousness were significantly associated with hypoxemia which is supported by various other studies as reported by the study by Onyango et al 3,18,24 Sah HD also highlighted different predictors for hypoxemia which were inability to feed and drink lethargy, tachypnea, and central cyanosis, chest in-drawing and grunting. 23 This research has shown that the cyanosis (94.737%), head nodding (96.99%), grunting (90.22%) were highly specific but all were less sensitive sign as seen variably in the previous studies.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The high sensitivity of fever, difficulty in breathing and cough was comparable with previous studies, while inability to feed was found specific as supported by Sah HD. 17,20,23 Findings of the present study revealed that cyanosis had a very high association whereas grunting; chest retractions, nasal flaring and impaired consciousness were significantly associated with hypoxemia which is supported by various other studies as reported by the study by Onyango et al 3,18,24 Sah HD also highlighted different predictors for hypoxemia which were inability to feed and drink lethargy, tachypnea, and central cyanosis, chest in-drawing and grunting. 23 This research has shown that the cyanosis (94.737%), head nodding (96.99%), grunting (90.22%) were highly specific but all were less sensitive sign as seen variably in the previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of hypoxemia was significantly more (42.8%) in severe pneumonia as compared to 24.5% in pneumonia, comparable previous studies. 17,20 The results were not comparable with the study of Alwadhi et al (50.9%) because of the fact that the definition of severe pneumonia used in their study was based on IMNCI guidelines, which uses a syndromic approach to identify sick children unlike the WHO algorithm used in present study. 21 The study showed the increasing sensitivity with higher respiratory rate and a statistical association of tachypnea with hypoxemia comparable to previous studies which showed that age specific increase in respiratory rate, were single most useful signs to predict hypoxemia.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…A similar cross-sectional study on determinants of hypoxemia in children associated with pneumonia by Ramawat and Sharma (2015) revealed that the prevalence of hypoxemia was 48% (29). As compared to our study, the cross-sectional study by Ramawat and Sharma (2015) found that the incidence of POH is comparable, even though differences in study design exist and is higher than the study done by Kumar Rao et al (2012). This might be due to the fact that it took into account only pediatric patients with acute respiratory tract infections.…”
Section: Discussioncontrasting
confidence: 49%
“…The prevalence of hypoxemia was found to be 23.8% in a cross-sectional study conducted by Kumar Rao et al ( 2012) on clinical predictors of hypoxemia in Indian children coming to the pediatric emergency room with an acute respiratory tract infection (28). A similar cross-sectional study on determinants of hypoxemia in children associated with pneumonia by Ramawat and Sharma (2015) revealed that the prevalence of hypoxemia was 48% (29). As compared to our study, the cross-sectional study by Ramawat and Sharma (2015) found that the incidence of POH is comparable, even though differences in study design exist and is higher than the study done by Kumar Rao et al (2012).…”
Section: Discussionsupporting
confidence: 47%